21st Century Good Neighbor Program: An Easily Generalizable Program to Reduce Social Isolation in Older Adults - Shashank Sandu; Siva Sreedhar; Linda Chang; Lindsay Cohen; Andrea Cruz; Heidi R. Olson; Radhika Sreedhar; Kayeromi Gomez; Alberto Carrion (Frontiers Media S.A., 2021)
Aim: In this once-in-a-lifetime humanitarian crisis, what does it mean to be a good neighbor? It means that as a community, we must address loneliness and barriers to care faced by vulnerable populations such as older adults. We share an inexpensive longitudinal experiential service-learning program implemented by health professions and undergraduate student volunteers that aims to help alleviate loneliness in older adults while imparting meaningful experiences to volunteers.Intervention Design and Setting: The 21st Century Good Neighbor Program is an observational cohort study of an experiential service-learning program started in May 2020, and this article shares the results collected after 1 year. This longitudinal, weekly phone call program was conducted in a single community setting in the Midwestern part of the United States. Older adults over the age of 60 served by a local community service agency (CSA) were invited to participate. Volunteers consisted of students 18 or older. Student volunteers made regular phone calls to a pair of older adults throughout the course of 1 year following standardized call scripts. The loneliness of the older adults was measured by volunteers using the 3-item UCLA Loneliness Assessment.Results: 261 older adults were engaged in conversations with a volunteer. A total of 1,391 calls were accepted by older adults and the median length of a welcomed call was 11 min. The average baseline loneliness score was 4.156 ± 1.41 and the prevalence of social isolation was 19.5%. There was no significant change in the UCLA loneliness score in the first year of follow up. However, a majority of volunteers (88%) agreed or strongly agreed that the program had a positive impact on them. In addition, the program identified 257 issues older adults faced that required follow-up. The most prevalent concerns referred to the community service agency by volunteers were issues related to utilities, food and transportation access.Conclusion: The 21st Century Good Neighbor Program is a unique intervention in which student volunteers and older adults paired by a community service agency forge relationships though a longitudinal phone call-based program. This easy-to-implement program provides another layer of support to identify and refer issues that impact social determinants of health. The added benefit of volunteer satisfaction in the setting of COVID 19 pandemic is heartening. We hope to continue to study the impact of this intervention on social isolation in this vulnerable population.